Stability analysis of single-phase grid-feeding inverters with PLL using Harmonic Linearisation and Linear Time Periodic (LTP) theory - Salis, Valerio; Costabeber, Alessando; Zanchetta, Pericle; Cox, Stephen M. (2016)
A general method for the stability analysis of power converters is presented in this paper. The method is based on Harmonic Linearisation and Linear Time Periodic (LTP) analysis techniques and a single-phase grid-feeding inverter with PLL is considered as case study. Although stability analysis has been developed using the average model of the converter, the obtained results can be extended to the switching model and it is possible to evaluate precisely the boundary between stability and instability.